(untitled) (Al-Mansour Journal, 2022)
Arabic language is the one of many languages that uses Harakat (damma, kas-ra, fat-ha, sukoon, tanween) or short vowel marks for the correct pronunciation that by his turn will affect the meaning of the word. In this language each word has deferent meaning based on the Harakat that can change the pronunciation. Harakat can be used on a single alphabet of these languages. We can write without them but the only the Professional people can interpret the correct meaning of the sentence. Thus in this paper we code each one of these Harakat and then we use the sequence of this Harakat to obtain the correct sequence of the secret message and developing the mechanism that can select the word with the proper Harakat that’s gives proper meaning based on huge database and provides mechanism also for high retrieval based on the requirement of the secret message.